Observation‐Driven Estimation of the Spatial Variability of 20th Century Sea Level Rise. Issue 3 (24th March 2018) - Hamlington, B. D.; Burgos, A.; Thompson, P. R.; Landerer, F. W.; Piecuch, C. G.; Adhikari, S.; Caron, L.; Reager, J. T.; Ivins, E. R.
Abstract: Over the past two decades, sea level measurements made by satellites have given clear indications of both global and regional sea level rise. Numerous studies have sought to leverage the modern satellite record and available historic sea level data provided by tide gauges to estimate past sea level rise, leading to several estimates for the 20 th century trend in global mean sea level in the range between 1 and 2 mm/yr. On regional scales, few attempts have been made to estimate trends over the same time period. This is due largely to the inhomogeneity and quality of the tide gauge network through the 20 th century, which render commonly used reconstruction techniques inadequate. Here, a new approach is adopted, integrating data from a select set of tide gauges with prior estimates of spatial structure based on historical sea level forcing information from the major contributing processes over the past century. The resulting map of 20 th century regional sea level rise is optimized to agree with the tide gauge‐measured trends, and provides an indication of the likely contributions of different sources to regional patterns. Of equal importance, this study demonstrates the sensitivities of this regional trend map to current knowledge and uncertainty of the contributing processes. Key Points: Regional sea level trends are computed using tide gauges and estimates of the structure of the processes contributing to sea level change The regional sea level trends are optimized to agree with the tide gauges, providing an indication of the contribution of different sources This study demonstrates the sensitivities of this regional trend map to current knowledge and uncertainty of the contributing processes